Poor reproductive performance associated with skin injuries of the male lesser mouse deer - Sriyanto; Saad, Mohd Zamri; Agungpriyono, Srihadi; Abu Bakar @ Zakaria, Md Zuki; Haron, Abd Wahid (Universiti Putra Malaysia Press, 2010)
Skin injury at the ventral part of the body and joints of hind limbs are common in lesser mouse deer in captivity, especially when kept in unsuitable cages. These animals showed unstable behaviour due to stress that could lead to their inability to mount during mating. The recovery was long due to the constant in-contact of the lesions to the environment. However, recovery can be aided by antibiotic and supportive therapies, which include fluid and nutritional supplementations which can substitute severe fluid and protein losses. Broad spectrum of antibiotic should be used to prevent secondary bacterial infection.